2020
DOI: 10.3389/fgene.2020.00987
|View full text |Cite
|
Sign up to set email alerts
|

CircDENND2A Promotes Non-small Cell Lung Cancer Progression via Regulating MiR-34a/CCNE1 Signaling

Abstract: The mechanism regulating non-small cell lung cancers (NSCLCs) is unclear. In this study, we aimed to determine the roles of DENN domain containing 2A (circDENND2A) in the progression of NSCLC. Circular RNAs (circRNAs) are composited by "head to tail" splicing of coding or non-coding RNAs (ncRNAs), whose crucial roles in human cancers had been revealed. CircDENND2A, a new circRNA, was revealed to induce cell proliferation and migration. Our data indicated that circDENND2A was a probable oncogene in human cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The protein encoded by CCNE1 gene participates and plays an important role in G1/S cell-cycle regulation. Recent study has found that the CCNE1 gene could serve as an oncogene and a poor prognostic factor in ovarian cancer and lung cancer (10)(11)(12). However, CCNE1 gene mutation has not been reported in BA or CMPT so far.…”
Section: Discussionmentioning
confidence: 98%
“…The protein encoded by CCNE1 gene participates and plays an important role in G1/S cell-cycle regulation. Recent study has found that the CCNE1 gene could serve as an oncogene and a poor prognostic factor in ovarian cancer and lung cancer (10)(11)(12). However, CCNE1 gene mutation has not been reported in BA or CMPT so far.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, CCNE1 and CHEK1 were proved to be related with the connection of the cell cycle and P53 and PI3K/AKT pathways. The study has also found that CCNE1 is one key gene which is enriched in P53 pathways, and the report of Zhang et al has also suggested that circDENND2A can regulate the activity of P53 pathways in lung cancer through the miR-34a/CCNE1 axis [ 26 , 27 ]. In addition, CHEK1 has been confirmed to have a direct link with P53 in colon cancer, and inhibited CHEK1 could significantly promote the apoptosis of P53-knockdown cancer cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA-microRNA-associated ceRNA has been confirmed as an important mode in progress of TNBC (Yang et al, 2018 ; Dong et al, 2020 ; Li et al, 2020 ), and CCNE1-associated ceRNA regulation appeared in several cancers (Zhang et al, 2019 , 2020 ). Thus, we inferred that lncRNA-microRNA-associated ceRNA hypothesis provided potential possibility of CCNE1 dysregulation in TNBC.…”
Section: Discussionmentioning
confidence: 99%